Ecological speciation in European whitefish is driven by a large‐gaped predator. Issue 3 (13th May 2020) - Öhlund, Gunnar; Bodin, Mats; Nilsson, Karin A.; Öhlund, Sven‐Ola; Mobley, Kenyon B.; Hudson, Alan G.; Peedu, Mikael; Brännström, Åke; Bartels, Pia; Præbel, Kim; Hein, Catherine L.; Johansson, Petter; et al.
Abstract: Lake‐dwelling fish that form species pairs/flocks characterized by body size divergence are important model systems for speciation research. Although several sources of divergent selection have been identified in these systems, their importance for driving the speciation process remains elusive. A major problem is that in retrospect, we cannot distinguish selection pressures that initiated divergence from those acting later in the process. To address this issue, we studied the initial stages of speciation in European whitefish ( Coregonus lavaretus ) using data from 358 populations of varying age (26–10, 000 years). We find that whitefish speciation is driven by a large‐growing predator, the northern pike ( Esox lucius ). Pike initiates divergence by causing a largely plastic differentiation into benthic giants and pelagic dwarfs: ecotypes that will subsequently develop partial reproductive isolation and heritable differences in gill raker number. Using an eco‐evolutionary model, we demonstrate how pike's habitat specificity and large gape size are critical for imposing a between‐habitat trade‐off, causing prey to mature in a safer place or at a safer size. Thereby, we propose a novel mechanism for how predators may cause dwarf/giant speciation in lake‐dwelling fish species.